An Orthogonal Protection Strategy for the Synthesis of Conotoxins Containing Three Disulfide Bonds - Hengyu Zhang; Lai Yue Chan; Huanhuan Zhang; Tao Jiang; David J. Craik; Wenqing Cai; Rilei Yu (Marine Drugs)
Disulfide bonds are crucial for stabilizing bioactive peptides such as conotoxins. We have developed a method for synthesizing conotoxins with three disulfide bonds using Mob, Trt, and Acm protection groups for regionally selective synthesis. This approach enabled the efficient synthesis of peptides with the desired disulfide bond connectivities independent of their sequences. Using our strategy, we synthesized five conotoxins, achieving yields of 20–30%. The results demonstrate the potential of our method for synthesizing complex peptides with multiple disulfide bonds.